2021
DOI: 10.1002/ange.202014766
|View full text |Cite
|
Sign up to set email alerts
|

Towards High‐Performance Zinc‐Based Hybrid Supercapacitors via Macropores‐Based Charge Storage in Organic Electrolytes

Abstract: Zn‐based aqueous supercapacitors are attracting extensive attention. However, most of the reported long‐life and high‐power performances are achieved with low Zn‐utilization (<0.6 %) and low mass loading in cathode (<2 mg cm−2). And, many obtained high energy densities are generally evaluated without considering the mass of Zn‐anode. Herein, we propose a Zn‐based hybrid supercapacitor, involving a metal organic framework derived porous carbon cathode, a Zn‐anode and an N, N‐dimethylformamide (DMF)‐based electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 75 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…35 Wang et al successfully clarify the charge storage mechanism of the MOF-PC (metal organic framework derived porous carbon) cathode of Zn-based hybrid SC (i.e., MOF-PC//Zn) by using in situ ATR-IR analysis in a nonaqueous electrolyte (0.5 M Zn-TFMS in dimethylformamide solution), which is found that the charge storage mechanism mainly based on the anions/cations adsorption and exchange in macropores. 36 These studies are based on the ionic kinetic mechanism of EDLCs with organic or ionic liquids as electrolytes. However, so far, the reports on the ionic dynamics mechanism of biomass carbon materials containing N and O functional groups in SCs in aqueous electrolytes and the chemical changes at the molecular level in electrochemical energy storage have not been revealed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…35 Wang et al successfully clarify the charge storage mechanism of the MOF-PC (metal organic framework derived porous carbon) cathode of Zn-based hybrid SC (i.e., MOF-PC//Zn) by using in situ ATR-IR analysis in a nonaqueous electrolyte (0.5 M Zn-TFMS in dimethylformamide solution), which is found that the charge storage mechanism mainly based on the anions/cations adsorption and exchange in macropores. 36 These studies are based on the ionic kinetic mechanism of EDLCs with organic or ionic liquids as electrolytes. However, so far, the reports on the ionic dynamics mechanism of biomass carbon materials containing N and O functional groups in SCs in aqueous electrolytes and the chemical changes at the molecular level in electrochemical energy storage have not been revealed in detail.…”
Section: Introductionmentioning
confidence: 99%